(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2024)
This study studies the complex relationships between maize growth, soil organic matter, and soil physico-chemcial properties, with an emphasis on biochar. It examines how soil organic matter affects pH, bulk density, Cation Exchange Capacity (CEC), porosity, and nutrient levels. Biochar and soil organic matter increase soil pH by decomposing organic anions. With biochar, increasing soil organic matter concentration reduces bulk density, improving soil structure, porosity, and water retention. By increasing Cation Exchange Capacity (CEC), biochar and soil organic matter improve soil nutrient retention and delivery, which is essential for soil fertility. As a soil organic matter component, biochar provides macro and micronutrients, boosting soil production. The study also highlights the importance of soil porosity in plant growth, with sandy soils having high porosity and leaching susceptibility and soil organic matter. However, loam soils, made of sand, clay, and silt, have a balanced porosity and soil organic matter concentration that makes them ideal for agriculture. These data show how organic matter, and biochar, affect maize growth and soil physico-chemical properties. This finding has major implications for protecting the environment and sustainable agriculture.